Information channel on municipal services: a perspectives from local affairs / Zaherawati Zakaria and Kamarudin Ngah - Zakaria, Zaherawati; Ngah, Kamarudin (Universiti Teknologi MARA, Kedah, 2018)
Past studies on customer satisfaction in Malaysia highlight low awareness from the public in municipal services. The previous studies mainly address the lack of efforts and initiatives of the authorities in organizing effective participation programs in waste management, cleanliness, drainage and culverts affairs. The Public Complaints Bureau stepped up efforts to promptly deal with complaints received from the public. On average, 50 per cent of complaints received were on the failure or delays in attending or responding to the needs of customers effectively. By using the quantitative methods approach, this study attempts to examine the factors that influence the community in Sungai Petani. The extent of satisfaction level in municipal services, both from internal customers and external customers attempt to establish association between customer satisfaction and social characteristics such as feedback towards complaint and information channel as resident and customer. Based on the findings, in order to make customer satisfaction increase on municipal services, future strategies need to be done by focusing on making customer satisfaction exercise more satisfactory and people more satisfy and participative